Civilization and pedagogy: Antonio Machado’s "Recuerdo infantil" - González de Ávila, Manuel (Tropelías: Review of Literary Theory and Comparative Literature, 2019)
Under the presumed candor and the modest simplicity of certain types of texts the reader believes to hear the anonymous and powerful voice of strayed truths, which not only do not belong to the author as part of his biographical legacy to culture, or at least he is not the only owner, but they also do not allow themselves to be imprisoned willingly in the netting of interpretations used in the history of literature. This gives rise, of course, to the capital question on the hermeneutic legitimacy of a reading that, placing in the foreground the signs of the text and conserving them in the course of its development, transcends them, nevertheless, towards the social and ideological horizon in which is inscribed all semiosic processes, including the poem and the emotion that the poem causes.